Handbook ilmu komunikasi / Charles R. Berger, Michael E. Roloff dan David R. Roskos-Ewoldsen ; Penerjemah, Derta Sri Widowatie ; Editor, Zakkie M. Irfan - BERGER, Charles R.; ROLOFF, Michael E.; ROSKOS-EWOLDSEN, David R.; DERTA Sri Widowatie; ZAKKIE M. Irfan (Nusa Media, 2014)
xx, 772 hlm. ; 24 cm